The dark side of simultaneous elections. The case of Sicily in 2022 Italian national elections - Danilo Di Mauro; Marco La Bella (QOE-IJES)
Instruments of “electoral engineering” such as compulsory voting, incentives and simultaneous multi-level voting, have become pretty common in contemporary democracies, especially in areas with low turnout rates. Simultaneous elections – i.e. the practice of establishing an election day when different governments (usually at local and national level, or including referendums) are elected – implies a reduction of costs for the institutions and increased empowerment for voters. However, these kinds of measures do not address the deep sentiments of disaffection for political institutions that often lie at the origin of non-voting. Moreover, simultaneous elections with different voting rules might confuse voters, thus increasing the number of invalid votes or no-choice. In order to examine the advantages and the threats of simultaneous elections, this study focuses on the recent case of the Italian general elections of 25th of September 2022, during which also the elections of the president and the regional assembly of Sicily were run simultaneously. This represents a regional context where atavistic disaffection and high volatility have marked the turnout rate of the last thirty years. By looking at the results of national elections within municipalities through a difference-in-difference strategy, we observe a slight increase in turnout rate in Sicilian municipalities. However, the number of both null and blank votes is significantly higher in Sicilian towns, suggesting a threatening effect of simultaneous voting.